(untitled) (Journal of the College of Education for Women, 2019)
Multi-nationalities companies are the main companies in the progressedcountries that improve the current technology and, thus, become the main source of it.These companies, in the first place, aim to increase the profits of itsinvestments to satisfy stock holders in the original countries to which these companiesbelong.It is a mean to interfere in the economic of countries especially the growingones and exploit their important natural resources. Since this research focus on thedangers of these companies, mechanism of its work and its dangers on the mostimportant natural resources of our country which is oil; therefore, the researchconfirm that this important natural treasure must be under an Iraqi control as aconcept to be implemented in the new constitution and it will be a new beginning inthe field of planning to get rid of the economic dependence.